FAKTOR-FAKTOR YANG MEMENGARUHI NILAI PERUSAHAAN NONKEUANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Rudi Setiadi Tjahjono; Ricky Wijaya (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2022)
This research was conducted to determine the effect of institusional ownership, profitability, liquidity, dividend policy, debt policy, firm size, effectiveness, efficiency on firm value in nonfinancial companies listed on Indonesia Stock Exchange. Previous research used 5 variables consisting institusional ownership, profitability, liquidity, dividend policy and debt policy. In this research, there are additional variables: firm size, effectiveness and efficiency. This research used 97 nonfinancial companies listed on the Indonesia Stock Exchange as a sample in the period 2018 until 2020. To determine the sample of companies is using purposive sampling method. This research used multiple regression as a method of analysis data. This result of this research indicates that institusional ownership, profitability and debt policy has a positive effect to firm value. Effectiveness and efficiency has a negative effect to firm value. While liquidity, dividend policy and firm size has no effect to firm value